Information systems evolution CAiSE Forum 2010, Hammamet, Tunisia, June 7-9, 2010, Selected extended papers - Soffer, Pnina; Proper, Erik (Lecture notes in business information processing, 2011)
This book constitutes the post-conference proceedings of the CAiSE Forum from the 22nd International Conference on Advanced Information Systems Engineering (CAiSE 2010), held in Hammamet, Tunisia, June 9, 2010. While the CAiSE conference itself focuses on papers that report on matured research, the CAiSE forum was created specifically as a platform to present fresh ideas, new concepts, and new and innovative systems, tools, and applications. The 22 papers presented in this volume were carefully reviewed and selected from 32 submissions. The reworked and extended versions of the original presentations cover topics such as business process management, enterprise architecture and modeling, service-oriented architectures, and requirements engineering.